The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ijmm.2017.3344
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of epitopes from influenza A virus hemagglutinin that induce broadly cross-reactive antibodies

Abstract: Influenza is the most common infectious disease and is caused by influenza A virus (IAV) infection. Hemagglutinin (HA) is an important viral protein of influenza A and is a major component of current IAV vaccines. The side effects associated with IAV vaccination are well studied; however, the HA‑induced immunopathological changes have remained largely elusive. The primary objective of the present study was to determine the tissue cross‑reactive epitopes of HA proteins. Monoclonal antibodies (McAbs) were genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Short peptides are good immunogens to study the immunogenicity and reactivity of virus heterophilic epitopes. For example, Li et al (2018) directly immunised mice with short peptides of the influenza virus and successfully screened and prepared mAbs. Gong et al (2016) coupled the short peptides P1-P6 of influenza virus H3N2 with keyhole limpet hemocyanin carrier proteins to increase the immunogenicity of peptides and induce a strong immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short peptides are good immunogens to study the immunogenicity and reactivity of virus heterophilic epitopes. For example, Li et al (2018) directly immunised mice with short peptides of the influenza virus and successfully screened and prepared mAbs. Gong et al (2016) coupled the short peptides P1-P6 of influenza virus H3N2 with keyhole limpet hemocyanin carrier proteins to increase the immunogenicity of peptides and induce a strong immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Polyglutamic acid was added to the carboxy terminus of positive peptides to facilitate their coating of ELISA plates (Li et al 2018). Each well was coated with 2 lg/mL of the peptide and incubated at 4°C overnight.…”
Section: Verification Of Indirect Elisa Localizationmentioning
confidence: 99%
“…Li et al (31) applied short-peptide immunization to the mice directly, and screened the prepared mAbs. In order to enhance immunogenicity, connection of polypeptides and macromolecular protein can also be used.…”
Section: Discussionmentioning
confidence: 99%
“…These short peptides can be also used as good immunogens to research different subtypes of influenza virus epitope vaccines. Li et al ( 31 ) applied short-peptide immunization to the mice directly, and screened the prepared mAbs. In order to enhance immunogenicity, connection of polypeptides and macromolecular protein can also be used.…”
Section: Discussionmentioning
confidence: 99%
“…Free fatty serves as a fuel for mitochondrial beta-type oxidation and can be esterified into triglycerides and cholesterol esters to form a unique spherical organelle named the lipid droplet. [39] Lipophagy is an unique selective autophagy that targets lipid droplets to regulate cellular lipid levels. [40] A recent study showed that lipophagy promotes ferroptosis by decreasing lipid storage and promoting lipid peroxidation.…”
Section: Lipophagy and Ferroptosismentioning
confidence: 99%